2006
DOI: 10.1007/s00330-006-0372-5
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal liver metastases: regional chemotherapy via transarterial chemoembolization (TACE) and hepatic chemoperfusion: an update

Abstract: Liver metastasis is one of the main problems encountered in colorectal cancer management as the liver is the most common metastatic site. Several treatment options are available, among which transarterial chemotherapy has proved effective in achieving some local tumour control, improving the quality of life through symptomatic control as well as survival time. The present paper is intended to provide an overview of the techniques, indications and results of regional chemotherapy, which comprises transarterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
0
13

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(79 citation statements)
references
References 61 publications
1
65
0
13
Order By: Relevance
“…The lipophilic nature of Lipiodol has the advantage of delivering the drugs directly to the targeted liver cells. 12 The embolizing agents administered significantly reduce flow through the relevant hepatic artery branch, although total occlusion is not achieved. Therefore, this significantly increases the time that the tumour cells are exposed to the chemotherapeutic agents and also increases the effective local concentration of these agents, thereby enhancing the activity of these agents.…”
Section: Current Trends In Interventional Treatment Of Colorectal Canmentioning
confidence: 99%
“…The lipophilic nature of Lipiodol has the advantage of delivering the drugs directly to the targeted liver cells. 12 The embolizing agents administered significantly reduce flow through the relevant hepatic artery branch, although total occlusion is not achieved. Therefore, this significantly increases the time that the tumour cells are exposed to the chemotherapeutic agents and also increases the effective local concentration of these agents, thereby enhancing the activity of these agents.…”
Section: Current Trends In Interventional Treatment Of Colorectal Canmentioning
confidence: 99%
“…[57][58][59] This suggests that sequential TACE with preoperative PVE could also be potentially beneficial in patients with colorectal metastases. To date, however, no study has reported the using of sequential TACE with preoperative PVE in this category of patients.…”
Section: Sequential Tace and Pvementioning
confidence: 99%
“…The concept of TACE has been used in the management of patients with liver metastases from colorectal cancer, breast carcinoma as well as patients with unresectable hepatocellular carcinoma (HCC). [12][13][14][15][16][17] Regarding unresectable CCC there are few studies addressing this issue, and the number of patients on the existing studies is relatively small. Another problem is that there are no studies about patients who were treated with Mitomycin C, Gemcitabine, Cisplatin or with a combination of them.…”
mentioning
confidence: 99%